PENGEMBANGAN UKS (UNIT KESEHATAN SEKOLAH) DENGAN IMPLEMENTASI SENAM DISMENOREA TAHUN 2021 - Ingka Kristina Pangaribuan; Marlina Simbolon; Dewi Sartika; Selfi Indah (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2021)
DEVELOPMENT OF UKS (SCHOOL HEALTH UNIT) WITH IMPLEMENTATION OF DYMENOROREAL GYSMS Ingka Kristina¬¬¬¬1, Marlina Simbolon¬¬¬¬2, Dewi Sartika¬¬¬¬2 Beautiful Selfies¬¬¬¬2HUSADA MEDAN PARTNER STIKES1STIKes Mitra Husada Medan2STIKes Mitra Husada Medan3STIKes Mitra Husada Medan ingka.kristina@gmail.com, Simbolon.marlina@yahoo.com,dewisartika2226@gmail.com,selvyindah555@gmail.com ABSTRACT Adolescents are individuals who when viewed physically are experiencing development and psychologically are experiencing emotional development, so that youth are human resources for development both now and in the future. As a candidate for the next generation who will replace the previous generation. Internationally, WHO refers to